Robust and Broadband Graphene Surface Plasmon Waveguide Coupler via Quantum Control - Chen, Yun; Huang, Wei; Ooi, Kelvin J. A.; Zhang, Wentao (Frontiers in Physics, 2022)
In this article, a novel graphene subwavelength waveguide coupler is designed based on the quantum control theory. Compared with metal surface plasmon polaritons (SPPs), graphene surface plasmon polaritons (GSPPs) have a smaller SPP wavelength and tunable properties. The dielectric load graphene plasmon waveguide (DLGPW) is used for designing to avoid the influence of the edge shape of the graphene nanoribbons on the waveguide mode. The coupling coefficient between the waveguides is calculated by using the coupled-mode theory (CMT). Due to the subwavelength properties of the graphene surface plasmons (GSP) and the robustness of the quantum control technique, our device is more compact and robust against perturbations of geometrical parameters under the premise of high transmission efficiency. The device we designed also has broadband characteristics, ranging from 30 THz to 40 THz, with high transmission efficiency when considering the transmission loss. We believe that our device will significantly contribute to integrated optics and photo-communication.